2019
DOI: 10.1016/j.jjcc.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction for 30-day heart failure-specific readmission or death after discharge: Data from the Korean Acute Heart Failure (KorAHF) registry

Abstract: Background: Identifying patients with acute heart failure (HF) at high risk for readmission or death after hospital discharge will enable the optimization of treatment and management. The objective of this study was to develop a risk score for 30-day HF-specific readmission or death in Korea. Methods: We analyzed the data from the Korean Acute Heart Failure (KorAHF) registry to develop a risk score. The model was derived from a multiple logistic regression analysis using a stepwise variable selection method. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 48 publications
2
37
0
6
Order By: Relevance
“…In this current study, patients with a history of hypertension had 17.2% lower incidence of HF than those with no hypertension. This finding is similar to a prospective study of acute HF patients in Korea where univariate analysis showed that patients who were prescribed beta-blockers, angiotensin converting enzyme inhibitors (ACEI), or angiotensin II receptor blockers (ARB) at discharge had relatively low hospitalization and mortality rates within 30 days [24]. This is because the antihypertensive agents have a similar pharmacological action to the beta blockers and ACEI or ARB.…”
Section: Discussionsupporting
confidence: 84%
“…In this current study, patients with a history of hypertension had 17.2% lower incidence of HF than those with no hypertension. This finding is similar to a prospective study of acute HF patients in Korea where univariate analysis showed that patients who were prescribed beta-blockers, angiotensin converting enzyme inhibitors (ACEI), or angiotensin II receptor blockers (ARB) at discharge had relatively low hospitalization and mortality rates within 30 days [24]. This is because the antihypertensive agents have a similar pharmacological action to the beta blockers and ACEI or ARB.…”
Section: Discussionsupporting
confidence: 84%
“…It was possible that the patient visited the nearest physician outpatient clinic when the patient had !3 H F points. Lim et al reported the risk score for the prediction of the 30-day HF readmission or death after hospital discharge [16]. Combined use of the risk score with our self-care point system may be more effective in preventing HF readmissions.…”
Section: Discussionmentioning
confidence: 98%
“…Among them, 446 (9.8%) had a 30-day readmission showing sensitivity (AUC of 0.710; 95% confidence interval, 0.685-0.735). 14 The results of the research conducted also found the same thing, there was a strong correlation between 6-MWT and a 30-day readmission. Sixty-one patients (52% female, mean age 46.9±14.1 years, 6-MWT distance 336.3±65 meters) had 27.6±12.8 days readmission, twenty one patients (45 , 3%) readmissions, with patients who readmissions having a shorter 6-MWD (p=0.007) and more likely to die than those who were not readmitted (RR=1.72, 95% CI= 1.13-2.62, p=0.003).…”
Section: Discussionmentioning
confidence: 59%